(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article presents a review of modern laser 3D technologies for processing metallic materials, which represent a leading direction in additive manufacturing. The fundamental principles of laser–metal interaction, melting and solidification mechanisms, and the importance of in-situ monitoring for quality assurance are discussed. The main laser-based 3D printing methods (SLS, SLM, DMLS, DED/LENS) are summarized, outlining their advantages, limitations, and areas of application. Special attention is paid to the requirements for metallic powders, ISO/ASTM standards, and the influence of laser parameters on microstructure and mechanical properties. The characteristics of widely used materials — titanium, aluminum, nickel alloys, stainless steels, cobalt-chromium, and copper systems — are systematized.